Real-life study on the effectiveness and safety of sofosbuvir/velpatasvir-based antiviral agents for hepatitis C eradication in Chinese patients - Jiayi Wang; Lingyao Du; Dongmei Zhang; Chen Zhou; Yilan Zeng; Miao Liu; Xing Cheng; Xiaona Song; Han Chen; Ning Han; Enqiang Chen; Hong Tang (Journal of Virus Eradication)
Background: Hepatitis C virus (HCV) eradication with sofosbuvir/velpatasvir (SOF/VEL) represents a significant advancement, offering hope for eliminating the virus in diverse patient populations. But real-world data on its effectiveness and safety remains scarce for patients with chronic hepatitis C (CHC) in China, especially those with HCV GT3b, cirrhosis, hepato-cellular carcinoma (HCC), or HCV/hepatitis B (HBV), HCV/HIV, or HCV/HBV/HIV coinfection. Methods: In this real-world prospective observational study, we recruited patients from the West China Hospital and Public Health Clinical Center of Chengdu in China. Patients included adults with with CHC and any genotype (GT), with or without cirrhosis, hepatocellular carcinoma (HCC), HCV/HBV, HCV/HIV, or HCV/HBV/HIV coinfection. Patients were administered SOF/VEL (400/100 mg) ± ribavirin (RBV) once daily for 12 weeks. The primary efficacy endpoint was sustained virological response at post-treatment week 12 (SVR12). Adverse events (AEs) were evaluated during treatment. Results: The study included 483 patients with HCV genotypes 1, 2, 3, 6 and uncertain ones. Among them, 35.4 % (171/483, ITT) and 36.7 % (166/452, mITT) received SOF/VEL + RBV. At the end of treatment , 99.2 % (ITT, 479/483) and 99.1 % (mITT, 448/452) of patients had undetectable HCV RNA. SVR12 rates were 92.8 % [intention to treat (ITT), 448/483] and 99.1 % [modified ITT (mITT), 448/452]. In the mITT analysis, SVR12 for patients with HCV GT3b, those with cirrhosis or HCC, and those coinfected with HBV/HIV was 99.2 % (130/131), 99.4 % (168/169), and 97.6 % (40/41), respectively. The albumin-bilirubin (ALBI) (−3.01 vs. −3.18 P < 0.001), Fibrosis-4 (FIB4) Index (2.53 vs. 1.88, P = 0.004) and AST to Platelet Ratio Index (APRI) (0.99 vs. 0.44, P < 0.001) scores showed a significant decrease from baseline to SVR12. No patients experienced grade 3–5 AEs. Conclusions: Although a high proportion of patients included in this study had HCV GT3b, cirrhosis, HCC, or HCV/HBV, HCV/HIV, or HCV/HBV/HIV coinfection, SOF/VEL ± RBV was highly effective and well tolerated in Chinese patients with CHC.